Strengthening co-founder partnerships: Applying couple therapy principles to STEM ventures - Overall, Jeffrey (American Journal of STEM Education, 2025)
Co-founder relationships are critical to entrepreneurial success, yet they often suffer from conflict and misalignment that threaten business outcomes. In this research, I integrate insights from attachment theory, couple therapy principles, and organizational psychology to explore the dynamics of co-founder partnerships and identify strategies for fostering resilience and collaboration. Evidence-based interventions, such as goal alignment, communication training, and proactive conflict resolution, are presented as practical tools to enhance partnership effectiveness. By cultivating self-awareness, clarifying shared objectives, and promoting open dialogue, co-founders can mitigate risks of dysfunction and strengthen their relational foundation. The main contribution to knowledge of this research is the novel integration of couple therapy principles within the dynamics of co-founder relationships. This research contributes to the growing literature on entrepreneurial relationships by offering a framework for understanding and optimizing co-founder dynamics, emphasizing their pivotal role in sustaining innovation and long-term organizational success.